1995
DOI: 10.1038/nm0895-761
|View full text |Cite
|
Sign up to set email alerts
|

Spectacle lenses alter eye growth and the refractive status of young monkeys

Abstract: The influence of visual experience on ocular development in higher primates is not well understood. To investigate the possible role of defocus in regulating ocular growth, spectacle lenses were used to optically simulate refractive anomalies in young monkeys (for example, myopia or nearsightedness). Both positive and negative lenses produced compensating ocular growth that reduced the lens-induced refractive errors and, at least for low lens powers, minimized any refractive-error differences between the two e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
268
1
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(281 citation statements)
references
References 23 publications
9
268
1
3
Order By: Relevance
“…[27][28][29][30][31][32][33] In particular, the negative-powered lenses imposed relative hyperopia on the treated eyes, which in response became more myopic than their fellow control eyes. In contrast, the positivepowered lenses imposed relative myopia, which initiated relative hyperopic shifts in the treated eye refractive errors.…”
Section: Refractive Development Is Regulated By Optical Defocusmentioning
confidence: 99%
“…[27][28][29][30][31][32][33] In particular, the negative-powered lenses imposed relative hyperopia on the treated eyes, which in response became more myopic than their fellow control eyes. In contrast, the positivepowered lenses imposed relative myopia, which initiated relative hyperopic shifts in the treated eye refractive errors.…”
Section: Refractive Development Is Regulated By Optical Defocusmentioning
confidence: 99%
“…This fact was unknown at the time of Helmholtz and thus there is no report that correlates a mechanism other. But today we know that both mechanisms are intimately linked (9)(10)(11)(12)(13) .…”
Section: The Mechanism Of the Ocular Emmetropizationmentioning
confidence: 99%
“…The classic experiments of Hung et al (12,13) , with placement of positive and negative lenses ("defocus" positive and negative, respectively) over the eyes of monkeys have shown that you can change the refractive state of eyes in minutes. Moreover, the posterior pole of younger eyes move with greater amplitude in the search for image focus, as shown in Figure 6.…”
Section: The Mechanism Of the Ocular Emmetropizationmentioning
confidence: 99%
“…In a variety of young animals, ocular growth is modulated by the visual environment (Hung et al, 1995;Irving et al, 1992;Schaeffel et al, 1988;Siegwart and Norton, 1993;Wallman et al, 1978). This modulation process, called emmetropisation, has been studied experimentally with induced refractive errors; myopia can be induced by covering young eyes with diffusers (form deprivation) or negative lenses (imposed hyperopic defocus), and hyperopia can be induced by the addition of positive lenses (imposed myopic defocus).…”
Section: Introductionmentioning
confidence: 99%